Productivity, efficiency and technological change in banking: empirical evidence from the Chinese banking sector - Sufian, Fadzlan (Inderscience, 2010)
By applying the non-parametric Malmquist Productivity Index method, this paper attempts to investigate the sources of productivity changes of China’s State-Owned and Joint-Stock Commercial Banks (JSCBs) during the period 2000–2005. The empirical findings suggest that the China’s banking sector has exhibited productivity progress attributed to the increase in efficiency. The empirical findings suggest that the State-Owned and the JSCBs have exhibited productivity progress of 5.9% and 0.3%, respectively. The second stage multivariate regression results suggest that profitability, income diversification, capitalization and loan intensity leads to a higher level of total factor productivity, technological change and efficiency, while risk is negatively related to the banks’ technological change levels.